Screening of Chickpea (Cicer arietinum L.) Genotypes under Water Stress Conditions (Plant Bulletin, 2025)
Ten genotypes of chickpeas (Cicer arietinum L.) were examined in this study for their ability to resist drought in both normal and water stress environments through the evaluation of numerous morpho-physiological characteristics at various growth stages. Genotypes were assessed for characteristics such as plant length, root length, chlorophyll index, number of seeds per plant, pod production, and seed weight under both normal and drought conditions during field experiments at Muhammad Nawaz Sharif University of Agriculture, Multan. Factorial Randomized Complete Block Design (RCBD) with three replications were used in this experiment. The analysis of variance showed highly significant (p
Keywords: abiotic stress